2014
DOI: 10.1104/pp.114.250837
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Binding E3 Ligase Mediates Iron Response in Plants by Targeting Basic Helix-Loop-Helix Transcription Factors  

Abstract: Iron uptake and metabolism are tightly regulated in both plants and animals. In Arabidopsis (Arabidopsis thaliana), BRUTUS (BTS), which contains three hemerythrin (HHE) domains and a Really Interesting New Gene (RING) domain, interacts with basic helix-loop-helix transcription factors that are capable of forming heterodimers with POPEYE (PYE), a positive regulator of the iron deficiency response. BTS has been shown to have E3 ligase capacity and to play a role in root growth, rhizosphere acidification, and iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
393
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(426 citation statements)
references
References 62 publications
(90 reference statements)
12
393
2
Order By: Relevance
“…Four other BHLH transcription factors, BHLH38, BHLH39, BHLH100, and BHLH101, are Fe responsive (Wang et al, 2007). BHLH100 and BHLH101 act separately from PYE and from BHLH38, BHLH39, and FIT, which interact to mediate regulation of root Fe uptake (Yuan et al, 2008) but all are implied in the regulation of Fe uptake or distribution between tissues (Long et al, 2010, Sivitz et al, 2012, Selote et al, 2015. The bHLH family of transcription factors thus plays an important role in Fe homeostasis.…”
Section: Iron Economy Involves Specific Response Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four other BHLH transcription factors, BHLH38, BHLH39, BHLH100, and BHLH101, are Fe responsive (Wang et al, 2007). BHLH100 and BHLH101 act separately from PYE and from BHLH38, BHLH39, and FIT, which interact to mediate regulation of root Fe uptake (Yuan et al, 2008) but all are implied in the regulation of Fe uptake or distribution between tissues (Long et al, 2010, Sivitz et al, 2012, Selote et al, 2015. The bHLH family of transcription factors thus plays an important role in Fe homeostasis.…”
Section: Iron Economy Involves Specific Response Programsmentioning
confidence: 99%
“…FIT and PYE are major regulators of root Fe uptake (for review, see Brumbarova et al, 2015). PYE associates with similar BHLH transcription factors (Selote et al, 2015). Four other BHLH transcription factors, BHLH38, BHLH39, BHLH100, and BHLH101, are Fe responsive (Wang et al, 2007).…”
Section: Iron Economy Involves Specific Response Programsmentioning
confidence: 99%
“…Hence, BTS might control Fe contents in plants by regulating the abundance of bHLH104 and ILR3. Recently, a study by Selote et al (2015) demonstrated that BTS could target ILR3 and bHLH115 but not bHLH104 for the 26S proteasomemediated degradation, using a cell-free degradation assay. However, the mutation of bHLH104 could partially complement the phenotype of BTS lesion (Figure 9), which suggested that the loss of bHLH104 might disrupt the formation of heterodimers with ILR3 and bHLH115 that function to activate the Fe deficiency responses in bts-2 plants.…”
Section: Bts and Bhlh104 Probably Function In The Same Pathway In Fe mentioning
confidence: 99%
“…The bHLH protein-dependent transcriptional regulation (FIT1-and PYE-dependent) plays a key role in the control of Fe uptake and homeostasis in plants (Colangelo and Guerinot, 2004;Long et al, 2010;Selote et al, 2015). Here, we show another kind of transcription factor that is from WRKY family participating in Fe deficiency response in Arabidopsis.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, some other bHLH proteins, e.g. POPEYE (PYE) and its homologs, are capable of forming heterodimers and play an important role in the regulation of Fe homeostasis probably independent of FIT1-mediated signaling pathway (Long et al, 2010;Selote et al, 2015). This evidence reveals that the bHLH transcription factors have key roles in regulating Fe uptake and homeostasis in plants.…”
mentioning
confidence: 89%